2017
DOI: 10.1016/j.resourpol.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of embedded non-safety regulation games in China's two types of coal mines through safety performance disparity, 1980–2014

Abstract: China has an appalling record of fatalities in its coal mining industry. Moreover, the fatalities observed in township and village coal mines (TVCMs) is much more terrible than that in state-owned coal mines (SOCMs). The safety performance of coal mines is influenced not solely by governmental safety regulation, but by their embedded non-safety regulation games with their internal and external related industries. Therefore, to better understand the safety performances disparity in SOCMs and TVCMs, an embedded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Early scholars applied evolutionary games to safe coal mine production; they mainly analysed the game between regulators and coal mining enterprises and identified insufficient investment in coal mine safety as the main cause of frequent accidents [22][23][24]. Some research studies have mainly focused on two-party evolutionary games [25][26][27][28][29]. However, the involved game participants are different; some games occur between coal mines, and some occur between coal mines and miners.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Early scholars applied evolutionary games to safe coal mine production; they mainly analysed the game between regulators and coal mining enterprises and identified insufficient investment in coal mine safety as the main cause of frequent accidents [22][23][24]. Some research studies have mainly focused on two-party evolutionary games [25][26][27][28][29]. However, the involved game participants are different; some games occur between coal mines, and some occur between coal mines and miners.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The characteristics of China's "rich in coal, poor in oil, and few in gas" energy reserves, and the energy production structure and energy consumption structure, which are dominated by coal production, mean that coal will continue to be China's main energy source into the future. However, although China has made significant progress in coal mining technology and safety equipment configuration [1], coal mine accidents still occur frequently [2,3], and coal mine safety production is facing difficulties. Previous studies found that human factors have become the leading cause of coal mine accidents [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we designed a questionnaire to obtain relevant data and employed empirical analysis to explore the relationship between work commitment, cultural emotion, and unemployment risk perception. This study is innovative in the following three respects: (1) based on the inherent connection between emotions and behavior, the concept of cultural emotions is defined, and the three-dimensional structure is clarified from a material level, behavioral level, and conceptual level, which constitutes an important breakthrough in the theoretical study of cultural emotions. (2) This study conducted in-depth research on the connotation, structure, and measurement of unemployment risk perception, clarified the three-dimensional structural framework, thus providing a theoretical reference and methodological support for the assessment of employees' perceptions of unemployment risk.…”
Section: Introductionmentioning
confidence: 99%
“…In order to ensure the sustainable development of the coal industry, we must pay attention to the safety of the coal industry. Currently, while the safety performance of coal mines in China has improved overwhelmingly year after year [1,2], coal-mine safety accidents are still frequent and the industry still has an appalling record of fatalities [3]. e losses caused by coalmine safety accidents are catastrophic.…”
Section: Introductionmentioning
confidence: 99%